Characterization of Research on Food Selectivity in ASD - Cassiano, Nathália Ferrer; Rodrigues Neto, João Manoel (Perspectivas em Análise do Comportamento, 2023)
Behavior analysis has contributed to a better understanding of issues that interfere in the repertoire of individuals with autism spectrum disorder. Dietary restrictions and selectivity are reported as behavioral relations present in ASD. This article aims to characterize studies on the eating behavior of individuals with ASD using the behavioral analysis framework and examines texts published from 2010 to 2022 in journals present in the SciELO database, besides books, official publications available online, scientific articles and monograph projects, dissertations, and theses available on Google Scholar. Studies with scientific and empirical content and with some type of experimental design were selected to highlight the importance of characterizing what has already been published by other researchers, what is already known, and evidence in regard to that subject, besides possible limitations of the studies.